2019
DOI: 10.1371/journal.pone.0214923
|View full text |Cite
|
Sign up to set email alerts
|

Persistent female genital mutilation despite its illegality: Narratives from women and men in northern Ghana

Abstract: Background Globally, an estimated two million women have undergone Female Genital Mutilation (FGM), and approximately four percent of women who have been circumcised live in Ghana. In the Bawku Municipality and Pusiga District, sixty one percent of women have undergone the procedure. This study therefore aimed at identifying the factors that sustain the practice of FGM despite its illegality, in the Bawku Municipality and the Pusiga District. Method This study used a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 33 publications
6
25
0
Order By: Relevance
“…Although this could be an outcome of social effects arising from the introduction of the 1994 law banning circumcision in Ghana and publicity about this law in the period following the 1995 survey. Further research has shown, however, that laws have had limited, if any, social impact [16,28] Survey research conducted in the 1990s was repeated in 2005, yielding results showing the persistence of the practice. Moreover, the relevance of social research on the practice is sustained by the fact that health problems associated with the practice are known to persist [29][30][31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this could be an outcome of social effects arising from the introduction of the 1994 law banning circumcision in Ghana and publicity about this law in the period following the 1995 survey. Further research has shown, however, that laws have had limited, if any, social impact [16,28] Survey research conducted in the 1990s was repeated in 2005, yielding results showing the persistence of the practice. Moreover, the relevance of social research on the practice is sustained by the fact that health problems associated with the practice are known to persist [29][30][31].…”
Section: Methodsmentioning
confidence: 99%
“…Research on female 'circumcision' not only has to take into account the place of the practice in the culture in question but also has to be foregrounded in a multifaceted analysis of the lives of those women whose genitals have become the subject of study [12]. This paper provides qualitative data from eld based study to explicate the gender dynamics of female circumcision in the Kassena-Nankana district of northern Ghana, a locality of northern Ghana that is known to have a high FGM prevalence [13][14][15][16]. Focus group discussions with women and men are employed to illustrate the gender roles that in uence the practice of female circumcision in a rural, traditional African setting.…”
Section: Introductionmentioning
confidence: 99%
“…Participants for seven of the focus group discussions were females selected according to age and marital status categories de ning polygamous unions (aged 25-35 and 35-49) and single unions (aged 25-35 and 35-49). There were two adolescent female groups and 2 adolescent male groups (20)(21)(22)(23)(24). Female marital status was chosen as a selection criteria based on the assumption that having co-wives will have an observed effect on circumcision status after marriage.…”
Section: Methodsmentioning
confidence: 99%
“…"Mothers can force their daughters to be circumcised just because her rivals [meaning: co-wives] are insulting her and her daughters." --Gomongo adolescent boys, aged [20][21][22][23][24][25] Maintaining mother to daughter traditions. Women point out that if the mother had undergone circumcision, daughters should also expect to undergo the practice.…”
Section: The Role Of Womenmentioning
confidence: 99%
See 1 more Smart Citation